Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Comparative Proteomic Insights into Low Molecular Weight Chitosan-Induced Drought Tolerance in Sugarcane - Gui Zhou; Xiao-Xia Liu; Li-Hang Qiu; Cheng-Lin Zou; Yang-Rui Li (Sugar Tech, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Silver Jubilee Special Issue: Sustainability through Diversification in the Sugar Industry - S. Solomon; Govind P. Rao; Yang Rui Li; Wirat Vanichsriratana; R. Manimeklai; Priyanka Singh; Cao Anh Duong (Sugar Tech, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

Development of Sugar Industry in China: R&D Priorities for Sustainable Sugarcane Production - Yang-Rui Li; Bao-Qing Zhang; Xiu-Peng Song; Qiang Liang; Krishan K. Verma; Dong-Mei Li (Sugar Tech, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Overexpression of α-Tubulin Gene of Sugarcane (Saccharum spp. hybrids), SoTUA, Enhances Tobacco Tolerance to Cold Stress - Jiao-Yun Chen; Bo Sun; Qaisar Khan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Proteome Based Comparative Investigation of a High Sucrose Sugarcane Mutant in Contrast to the Low Sucrose Mother Variety by Using TMT Quantitative Proteomics - Qaisar Khan; Ying Qin; Dao-Jun Guo; Zhen Lu; Xian-Qiu Xie; Li-Tao Yang; Qiang Liang; Xiu-Peng Song; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Sugar Tech Special Issue: History of Sugarcane Breeding, Germplasm Development and Related Molecular Research - Prakash Lakshmanan; Phillip Jackson; G. Hemaprabha; Yang Rui Li (Sugar Tech, 2022)

Characterization of Exotic, Native and Wild-Type Genotypes of Sugarcane (Saccharum spp. Hybrids) for Internal Nitrogen Use Efficiency Under Different Nitrogen Levels - Muhammad Anas; Krishan K. Verma; Ikram Ul Haq; Muhammad Naeem; Qiang Li; Fen Liao; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Impact of Sugarcane–Legume Intercropping on Diazotrophic Microbiome - Manoj Kumar Solanki; Fei-Yong Wang; Chang-Ning Li; Zhen Wang; Tao-Ju Lan; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2020)

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Beneficial Linkages of Endophytic Burkholderia anthina MYSP113 Towards Sugarcane Growth Promotion - Mukesh Kumar Malviya; Manoj Kumar Solanki; Chang-Ning Li; Reemon Htun; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Application of Multi-rotor Unmanned Aerial Vehicle Application in Management of Stem Borer (Lepidoptera) in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Zhen-Qiang Qin; De-Wei Li; Chun-Yan Wei; Jin-Ju Wei; Yang-Rui Li; Xiu-Peng Song (Sugar Tech, 2019)

Physiological and Molecular Analysis of Sugarcane (Varieties—F134 and NCo310) During Sporisorium scitamineum Interaction - Pratiksha Singh; Qi-Qi Song; Rajesh Kumar Singh; Hai-Bi Li; Manoj Kumar Solanki; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Molecular Cloning and Expression Analysis of ScTUA Gene in Sugarcane - Bao-Qing Zhang; Min Shao; Yong-Jian Liang; Xing Huang; Xiu-Peng Song; Hu Chen; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Impact of Seed Coating Agents on Single-Bud Seedcane Germination and Plant Growth in Commercial Sugarcane Cultivation - Yong-Jian Liang; Xiao-Qiu Zhang; Liu Yang; Xi-Hui Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Molecular Cloning and Expressional Analysis of Five Sucrose Transporter (SUT) Genes in Sugarcane - Jun-Qi Niu; Jing-Li Huang; Thi-Thu Phan; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Analysis of Sedimentary Components in Post-haze Concentrated Sugarcane Juice - Rui-Jing Qu; Kai Li; Fang-Xue Hang; Wen Li; Cai-Feng Xie (Sugar Tech, 2018)

Isolation, Transformation and Overexpression of Sugarcane SoP5CS Gene for Drought Tolerance Improvement - Jian Li; Thi-Thu Phan; Yang-Rui Li; Yong-Xiu Xing; Li-Tao Yang (Sugar Tech, 2018)

Production of Humic Acid by a Bacillus megaterium Strain Using Vinasse - Nan Li; Zhi-Nian Deng; Yuan-Wen Wei; Hui-Qing Cao; Yang-Rui Li (Sugar Tech, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Differential Effects of Cold Stress on Chloroplasts Structures and Photosynthetic Characteristics in Cold-Sensitive and Cold-Tolerant Cultivars of Sugarcane - Su-Li Li; Zhi-Gang Li; Li-Tao Yang; Yang-Rui Li; Zhen-Li He (Sugar Tech, 2018)

Identification and Efficiency of a Nitrogen-fixing Endophytic Actinobacterial Strain from Sugarcane - Zhen Wang; Manoj Kumar Solanki; Fei Pang; Rajesh Kumar Singh; Li-Tao Yang; Yang-Rui Li; Hai-Bi Li; Kai Zhu; Yong-Xiu Xing (Sugar Tech, 2017)

Influence of Inoculation of Leifsonia xyli subsp. xyli on Photosynthetic Parameters and Activities of Defense Enzymes in Sugarcane - Xiao-Qiu Zhang; Yong-Jian Liang; Kai Zhu; Chao-Xing Wu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Effects of Cold Stress on Root Growth and Physiological Metabolisms in Seedlings of Different Sugarcane Varieties - Bo Sun; Guang-Ling Liu; Thi Thu Phan; Li-Tao Yang; Yang-Rui Li; Yong-Xiu Xing (Sugar Tech, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Intercropping in Sugarcane Cultivation Influenced the Soil Properties and Enhanced the Diversity of Vital Diazotrophic Bacteria - Manoj Kumar Solanki; Zhen Wang; Fei-Yong Wang; Chang-Ning Li; Tao-Ju Lan; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Editorial-The Sugar Industry of Asian Region - S. Solomon; Yang-Rui Li (Sugar Tech, 2016)

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Economic Impact of Stem Borer-Resistant Genetically Modified Sugarcane in Guangxi and Yunnan Provinces of China - Jie Ye; Ying-Ying Yang; Li-Ping Xu; Yang-Rui Li; You-Xiong Que (Sugar Tech, 2016)

Evaluating Sugarcane Productivity in China over Different Periods Using Data Envelopment Analysis and the Malmquist Index - Jie Ye; You-Xiong Que; Yang-Rui Li; Li-Ping Xu (Sugar Tech, 2016)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Nitrogen-Fixing and Plant Growth-Promoting Ability of Two Endophytic Bacterial Strains Isolated from Sugarcane Stalks - Yong-Xiu Xing; Chun-Yan Wei; Yao Mo; Li-Tao Yang; Si-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Change of Polysaccharide Content and Its Relation with Nitrogen Level in Sugarcane Leaves Under Nitrogen-Fixing Bacteria Inoculation and Nitrogen Supply - Xi-Hui Liu; Hui-Ping Ou; Rong-Zhong Yang; Rong-Hua Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Isolation, Characterization and Promoter Analysis of Cell Wall Invertase Gene SoCIN1 from Sugarcane (Saccharum spp.) - Jun-Qi Niu; Ai-Qin Wang; Jing-Li Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Effect of Drought Stress on Anatomical Structure and Chloroplast Ultrastructure in Leaves of Sugarcane - Feng-Juan Zhang; Kun-Kun Zhang; Cheng-Zhong Du; Jian Li; Yong-Xiu Xing; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Research and Development Priorities for Sugar Industry of China: Recent Research Highlights - Yang-Rui Li; Li-Tao Yang (Sugar Tech, 2015)

Sugarcane Agriculture and Sugar Industry in China - Yang-Rui Li; Li-Tao Yang (Sugar Tech, 2015)

Physiological and Biochemical Characteristics Related to Cold Resistance in Sugarcane - Bao-Qing Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Effects of Exogenous Abscisic Acid on Cell Membrane and Endogenous Hormone Contents in Leaves of Sugarcane Seedlings under Cold Stress - Xing Huang; Ming-Hui Chen; Li-Tao Yang; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Effects of Vinasse and Press Mud Application on the Biological Properties of Soils and Productivity of Sugarcane - Shang-Dong Yang; Jun-Xian Liu; Jun Wu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Combined application of NPK on yield quality of sugarcane applied through SSDI - Lin Xu; Hai-Rong Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Soluble acid invertase and sucrose phosphate synthase: Key enzymes in regulating sucrose accumulation in sugarcane stalk - You-Qiang Pan; Hai-Ling Luo; Yang-Rui Li (Sugar Tech, 2009)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Fusion insect-resistant gene mediated by matrix attachment region (MAR) sequence in transgenic sugarcane - Zhi-Nian Deng; Yuan-Wen Wei; Wei-Li Lü; Yang-Rui Li (Sugar Tech, 2008)

Effects of molybdenum on nitrogen metabolism of sugarcane - Li -Ping Wei; Yang -Rui Li; Li -Tao Yang (Sugar Tech, 2007)

Differential Gene Expression in Sugarcane Regulated by Ethephon at Early Growth Stage - Yuan-Wen Wei; Chun-Jin Hu; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2006)

Sugar industry in China: R & D and policy initiatives to meet sugar and biofuel demand of future - Yang-Rui Li; Yuan-An Wei (Sugar Tech, 2006)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

Cloning of three members of acc synthase gene family in sugarcane - Ai-Qin Wang; Li-Tao Yang; Zi-Zhang Wang; Yu-Tuo Wei; Long-Fei He; Yang-Rui Li (Sugar Tech, 2006)

Identification of a new nitrogen fixing endo-bacterium strain isolated from sugarcane stalk - Yong-Xiu Xing; Li-Tao Yang; Si-Liang Huang; Yang-Rui Li (Sugar Tech, 2006)

Status and trends of sugar industry in China - Yuan-An Wei; Yang-Rui Li (Sugar Tech, 2006)

Trehalose synthase gene transfer mediated byAgrobacterium tumefaciens enhances resistance to osmotic stress in sugarcane - Zi-Zhang Wang; Shu-Zhen Zhang; Ben-Peng Yang; Yang-Rui Li (Sugar Tech, 2005)

Heralding a new era for sugar industry in China: Post IS-2004 scenario - Yang-Rui Li (Sugar Tech, 2005)

Chemical ripening of sugarcane: global progress and recent developments in China - S. Solomon; Yang-rui Li (Sugar Tech, 2004)

Beneficial effects of ethephon application on sugarcane under sub-tropical climate of China - Yang-rui Li (Sugar Tech, 2004)

China: An emerging sugar super power - Yang-rui Li (Sugar Tech, 2004)

Minimizing phenol pollution in sugarcane stem apical meristem culture - Cheng-Mei Huang; Yang-Rui Li; Yan-Ping Ye (Sugar Tech, 2003)

Endogenous hormone levels at technical maturing stage of sugarcane - Rui-liang Yao; Yang-rui Li; Gui-rong Zhang; Li-tao Yang (Sugar Tech, 2002)